Pharmacokinetics and Pharmacodynamics of Immediate-Release Versus Extended-Release Guanfacine in Adult Daily Smokers. Issue 2 (March 2019) - Verplaetse, Terril L.; Roberts, Walter; Moore, Kelly E.; Peltier, MacKenzie R.; Oberleitner, Lindsay M.; McKee, Sherry A.
Abstract: Background: Guanfacine is Food and Drug Administration approved for hypertension and attention-deficit hyperactivity disorder and has been used off-label for migraine prophylaxis, heroin withdrawal, and more recently smoking cessation. Previous studies have shown positive effects of 3 mg/d of immediate-release (IR) guanfacine on smoking outcomes, but the dose equivalency of the IR and extended-release (ER) formulations is unknown. Procedures: A within-subject design was used to compare the pharmacokinetics and pharmacodynamics of 3 mg/d of IR, 4 mg/d of ER, and 6 mg/d of ER guanfacine in adult daily smokers (n = 5). Plasma medication levels, vital signs, cigarettes per day, tobacco craving, and adverse events were assessed. Medication was titrated to stable dosing after each laboratory day (3 mg/d IR, then 4 mg/d ER, then 6 mg/d ER). Results: Plasma medication levels did not differ between the 3 mg/d of IR and 4 mg/d of ER doses after 24 hours from last dose and were highest at the 6 mg/d of ER dose (3 mg/d IR: M = 3.40 ng/mL, SE = 0.34 vs 4 mg/d ER: M = 3.46 ng/mL, SE = 0.67 vs 6 mg/d ER: M = 5.92 ng/mL, SE = 1.02). All doses of guanfacine decreased heart rate and blood pressure from baseline. Absolute values of cigarettes per day (6 mg/d ER) and tobacco craving (4 and 6 mg/d ER) were lowest with the ER formulations. Treatment-emergent adverse events were subject rated as minimal to mild, except dry mouth. Conclusions: We demonstrated similar pharmacokinetic profiles between 3 mg/d of IR guanfacine and 4 mg/d of ER guanfacine, as hypothesized. All doses of guanfacine were well tolerated.